Leveraging visualizations with systems for operational and strategic decision-making - Cuthbert, Carol Elaine (Rhodes University, Faculty of Commerce, Rhodes Business School)
Dynamic capability-enhancing technology, Subject Matter Experts (SMEs), System Experts (SEs) in planning and forecasting, and big data used for sensemaking combine to enable knowledge-based management decisions in interdisciplinary teams, increasing competitive advantage. This research extended Contingent Resource-based Theory CRBT by focusing on visualization's role in this process. SMEs and SEs configure assumptions, with visualizations, in an interdisciplinary team to enable planning within the context of legal practice management systems. The study employed a mixed-method sequential explanatory design. An initial quantitative component determining which types of decision-making information technology contribute to the competitiveness of a firm was undertaken. Niche systems were found to increase technological dynamic capability through their highly configurable workflow tools, which provide customization capabilities and the ability to react to a changing environment quickly. Niche systems differentiated through process automation were found to be the aspect to focus on in a qualitative research study. A knowledge-sharing process model was developed from the literature, and this was overlayed with visualization as the new knowledge-sharing enabler. Then, a thematic qualitative study of interviews focusing on SMEs' and SEs' use of visualization in legal and financial system implementation was employed to establish the extent to which this process occurs in legal financial transformation projects. Seven subject matter experts and four system experts in legal transformation implementations were interviewed regarding using visualization to facilitate communication, verification, and process configuration during the knowledge-sharing process. The research illustrated how (1) low code systems data, (2) people, and (3) data enable the creation, sharing, and configuration of knowledge in practice in the legal practice management context. Recommendations for further research were made to automate refining budgeting and forecasting assumptions. This enables management to arrive at more accurate forecasts by refining assumptions and producing the resultant profit and loss reports visually in heat maps depicting variance between the forecast and actual profit and loss reports. The SMEs provide feedback, and the system cycles between multiple assumption iterations, reducing the variance and enhancing management decision-making. Visualization was found to assist the knowledge-sharing process through (1) verification, (2) process enablement, and (3) communication for decision-making. This research highlighted the value of variance heat maps and other visualizations and workflows in making planning assumptions explicit, thereby enhancing forecasting accuracy.
Keywords: Information visualization; Subject-matter expert; Automated decision-making; Strategic planning; Knowledge sharing; Practice management system